Validity of two occlusal indices for determining orthodontic treatment needs of patients treated in a public university in Belo Horizonte, Minas Gerais State, Brazil Validade de dois índices oclusais na determinação de necessidade de tratamento ortodôntico em pacientes tratados em uma universidade pública em Belo Horizonte, Minas Gerais, Brasil - Rodrigo Norremose Costa; Mauro Henrique Nogueira Guimarães de Abreu; Claudia Silami de Magalhães; Allyson Nogueira Moreira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The aim of the present study was to validate the dental aesthetic index (DAI) and index of complexity, outcome and need (ICON) based on the opinions of a panel of Brazilian orthodontists. A comparison of these two orthodontic treatment need indices was carried out based on the consensus of a panel of 20 experienced orthodontists. A set of 108 study casts representing the full spectrum of malocclusions was selected. A calibrated examiner scored the casts for both indices. The orthodontists individually rated the casts regarding the degree of orthodontic treatment need. The panel's mean rating of the need for treatment was used as the gold standard for evaluating the validity of the indices. The accuracy of the indices, as reflected in the area under receiver-operating characteristic curves, was high: DAI = 81.83% (95%CI: 71.21-92.44); ICON = 88.75% (95%CI: 78.57-98.92). Although the accuracy of the ICON was higher than that of the DAI, both indices are recommended for determining orthodontic treatment need in Brazil. O objetivo do presente estudo foi validar os índices dental aesthetic index (DAI) e index of complexity, outcome and need (ICON) a partir da opinião de um painel de ortodontistas brasileiros. A comparação desses dois índices de necessidade de tratamento ortodôntico foi feita baseada no consenso de um painel de 20 experientes ortodontistas. Um conjunto de 108 modelos de estudo representando uma grande variedade de tipos de maloclusão foi selecionado. Um examinador calibrado mensurou os modelos para ambos os índices. Os ortodontistas, de forma individual, avaliaram a necessidade de tratamento ortodôntico de cada modelo. O valor médio do painel de ortodontistas em relação à necessidade de tratamento foi utilizado como padrão-ouro para validação dos índices. Os valores de acurácia dos índices, medidos pela curva de característica de operação do receptor, foram altos: DAI = 81,83% (IC95%: 71,21-92,44); ICON = 88,75% (IC95%: 78,57-98,92). Embora a acurácia do ICON tenha sido mais alta do que a do DAI, ambos os índices são recomendados para determinar a necessidade de tratamento ortodôntico no Brasil.